Zero-Valent Iron-Sand Filtration Reduces Escherichia coli in Surface Water and Leafy Green Growing Environments - Kim, Seongyun; Bradshaw, Rhodel; Kulkarni, Prachi; Allard, Sarah; Chiu, Pei C.; Sapkota, Amy R.; Newell, Michael J.; Handy, Eric T.; East, Cheryl L.; Kniel, Kalmia E.; Sharma, Manan (Frontiers in Sustainable Food Systems, 2020)
Surface water is used for irrigation by farmers. However, surface waters may be a source of bacterial foodborne pathogens which contaminate fresh produce intended for human consumption. Proposed but not finalized standards for microbial quality of irrigation water through the Produce Safety Rule (PSR) of the Food Safety Modernization Act (FSMA) in the US emphasize the need for effective reduction of levels of pathogens in surface water intended to be used on fruit and vegetable crops. This study evaluated a zero-valent iron (ZVI)-sand filtration system to reduce E. coli populations in pond water and those transferred to growing spinach plants in a field trial. Six filtration events were conducted with the same ZVI-sand or sand (S) laboratory filtration systems. Filtration systems were constructed by connecting 4 PVC pipes (1.25 L) together. ZVI-sand filters contained 50% ZVI/ 50% sand (0.43-0.60 mm particle size), while sand filters contained 100% sand (0.45-55 mm particle size). In each event, autoclaved pond water (PW) inoculated with E. coli (ca. 4 log CFU/ml) – 8 L - was pumped (1 L/min) through each filter followed by uninoculated autoclaved PW (15 L) with samples taken throughout the filtering process for enumeration of E. coli. Data were fit to a linear model to determine reductions of E. coli levels. ZVI-sand filtration removed significantly (p < 0.05) more E. coli (1.1 log CFU) compared to sand filtration. For ZVI-sand-filtered water, there was a statistically significant (p < 0.05) difference of E. coli removal from early trials (trials 1-3, average removal 96%) than in later trials (trial 4-6, average removal 44%), suggesting that age of the ZVI-sand filters influences E. coli inactivation. Overall, ZVI-sand and sand filtration reduced E. coli populations by 70% and -10%, respectively, indicating that ZVI filtration lowered or inactivated E. coli populations while sand filters accumulated E. coli. Field trials showed that soil and spinach plant samples irrigated with ZVI-sand-filtered water had significantly lower E. coli levels than soils irrigated with sand-filtered water or unfiltered control water. Overall, ZVI-sand filtration significantly reduced E. coli populations in water compared to sand filtration.